1991
DOI: 10.1051/rnd:19910202
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cells and the G2 to M-phase transition in sheep oocytes

Abstract: de I ir -amanitine achèvent aussi leur maturation. Des ovocytes dénudés ou non ont été cultivés sur la granulosa de parois folliculaires pour tester l'influence de la transcripdon dans la granulosa sur la progression de la méiose, Aucun effet de l'a-amanitine n a été détecté sur la maturation des ovocytes des 2 groupes. Nous concluons que la transcription dans le cumulus est essentielle pour permettre la traduction des messages des protéines du cycle cellulaire stockés dans les ovocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…In subsequent studies in our laboratory, however, we have demonstrated that DRB can be replaced at intervals up to 8 h without a significant reduction in its effectiveness (Martus and Farin, 1993). The observation that cumulus cell-oocyte complexes, rather than cumulus-free oocytes, must be present for DRB-mediated inhibition of maturation is consistent with previous studies in the ewe, cow, and pig in which a-amanitin was used to block GVBD (Osborn and Moor, 1983; Moor and Crosby, 1986;Galli and Moor, 1991;Meinecke and Meinecke-Tillmann, 1993).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In subsequent studies in our laboratory, however, we have demonstrated that DRB can be replaced at intervals up to 8 h without a significant reduction in its effectiveness (Martus and Farin, 1993). The observation that cumulus cell-oocyte complexes, rather than cumulus-free oocytes, must be present for DRB-mediated inhibition of maturation is consistent with previous studies in the ewe, cow, and pig in which a-amanitin was used to block GVBD (Osborn and Moor, 1983; Moor and Crosby, 1986;Galli and Moor, 1991;Meinecke and Meinecke-Tillmann, 1993).…”
Section: Discussionsupporting
confidence: 89%
“…The data presented herein lend support to the hypothesis (Galli and Moor, 1991) that gonadotropins mediate a transcriptional event to initiate GVBD in bovine oocytes. These observations do not imply, however, that in the absence of gonadotropins bovine oocytes will not undergo GVBD.…”
Section: Adenosinesupporting
confidence: 83%
“…Second, the metabolic consequences of these signaling events must be transmitted to the oocyte through physical interactions at the follicle cell-oocyte interface. In view of recent evidence suggesting that the oocyte can influence the function of surrounding granulosa cells (Buccione et al, 19901, and that the regulation of meiotic maturation requires transcriptional and translational activity within the cumulus (Galli and Moor, 1991;Motlik et al, 19891, connectivity within this heterocellular complex must now be considered as a complex phenomenon involving bidirectional signaling. It is the purpose of this study to evaluate our current knowledge of the types of physical associations that exist between follicle cells, and the oocyte in mammals based on classical structural analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The rates of in vitro maturation of mammalian oocytes including mice, cattle, and sheep are low compared with oocytes matured in vivo 28‐30 . This might be due to poor nuclear maturation caused by inadequate culture conditions 31‐34 .…”
Section: Discussionmentioning
confidence: 99%
“…The rates of in vitro maturation of mammalian oocytes including mice, cattle, and sheep are low compared with oocytes matured in vivo. [28][29][30] This might be due to poor nuclear maturation caused by inadequate culture conditions. [31][32][33][34] Several factors are included in culture media to improve the success rate of in vitro maturation.…”
Section: Discussionmentioning
confidence: 99%